Peer Tutoring Model in Enhancing Student Learning Outcomes at the Educational Action Research - Ishaka, Humaira (Journal of Foreign Language Teaching and Learning, 2026)
Background: There has been a limited use of engaging, student-centered instructional strategies in Educational Research courses. Conventional lecture-based approaches often restrict students’ active participation and hinder the development of research literacy and collaborative learning skills. To address this issue, this study examines peer tutoring as an alternative instructional approach to support active learning and conceptual understanding. Objective: The main objective of this study is to examine the effectiveness of peer tutoring in enhancing students’ understanding and engagement in Educational Research courses. Specifically, it aims to assess whether peer tutoring can improve learning outcomes and contribute to a more inclusive and interactive classroom environment. Methods: The study employed a quasi-experimental design involving 58 sixth-semester students: 30 from the English Education Study Program and 28 from the Indonesian Language Education Program. Two groups were formed—an experimental group that received instruction through peer tutoring, and a control group that received conventional teaching methods. Data were analyzed using quantitative techniques to compare learning outcomes between the two groups. Findings: The peer tutoring method significantly improves students' mastery of concepts in Educational Action Research, particularly in identifying research problems, formulating research questions, and designing classroom-based inquiry. Students in the experimental group demonstrated higher levels of engagement, collaboration, and academic achievement compared to those in the control group. Conclusion: The results indicate that peer tutoring is an effective instructional strategy for improving students’ learning outcomes in Educational Action Research courses. Pedagogically, peer tutoring supports active engagement, collaborative learning, and deeper understanding of research concepts, suggesting its potential application in other research-based and methodology courses in higher education. Future studies are encouraged to investigate the long-term impact of peer tutoring, explore its implementation across disciplines, and incorporate qualitative data to deepen insights into students’ learning experiences.